(untitled) (AYUSHDHARA, 2020)
Amavata is one of the crippling diseases. It is the systemic disorder in which pathogenic constituents are mainly Aama and Vata. The symptoms of Amavata are identical to Rheumatoid arthritis and Rheumatic fever. According to Ayurveda, Amavata is the disease which is mentioned under the category of Vata- Kaphaja vyadhi. Research has proven that Ayurvedic treatment is effective in the management of Amavata. Present case study was done on the female patient of Amavata, we found that Ayurvedic medicines improve Jatharagni and leads to the formation of other Dhatu as well as stop the formation Aam. In this study, patient is having many complaints such as joint pain, joint stiffness, cough, breathlessness, hoarseness of voice etc. Patient was given Ayurvedic medicines such as Suvarnabhasma, Sihnad Guggul, Amavatari Rasa and some Pancharkarma therapy such as Hrudyabasti, Nasya. Patient was feeling much better than earlier and she felt that about 95% of her symptoms got decreased. From the modern aspect, the non-steroidal anti-inflammatory drugs (NSAID`S) and disease modifying anti-rheumatic drugs (DMARD`S) are the main stay in this condition, however they have serious adverse effects and have limitations for long term therapy. Continuous use of allopathic drugs leads to symptoms like constipation, nausea, abdominal discomfort. So we stopped the allopathic medicine and started above mentioned Ayurvedic medicine and Panchakarma treatment and gradually alleviated above symptoms.